Repositioning Cities as Innovative Ecosystems: Integrating Digi-tal Infrastructure and Technology-Based Entrepreneurship in Urban Contexts - Harahap, Muhammad Ade Kurnia; Suherlan; Az Zaakiyyah, Hizbul Khootimah (Technology and Society Perspectives (TACIT), 2025)
This study aims to critically analyze how the integration of digital infrastructure and technology-based entrepreneurship can drive the repositioning of cities as innovative ecosystems within modern urban contexts. Employing a qualitative approach through a literature review method, this research examines 33 scholarly articles selected from 50 academic sources obtained via Google Scholar and other credible databases, published between 2020 and 2025. The findings reveal that the successful repositioning of cities is heavily influenced by the synergy between the availability of digital infrastructure, the activation of technology-driven entrepreneurship, collaborative governance, and the involvement of key actors such as government, universities, communities, and the business sector. Case studies from cities like Tallinn, Surabaya, Jakarta, and Bandung reinforce the argument that transforming cities into innovative ecosystems requires a systemic, theory-based approach that emphasizes social sustainability. This research offers both theoretical and practical contributions to the formulation of urban policies aimed at fostering cities as collaborative, digital, and innovation-driven spaces.